Bullying through social media A field sociology study at Damascus University Department of Sociology as a model (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
Until recently, bullying practices were limited to verbal bullying, such as giving up titles, physical bullying such as hitting, and social bullying as isolating a person and excluding him from social activities. Hypothetically, a large scale in the life of each of us (such as Facebook, Twitter, Instagram, Telegram, and chat rooms), plays a big role in the emergence of a new type of bullying, which is electronic bullying. The current research deals with a field study on electronic bullying through social media, the role of gender and the duration of time spent on social media, in the increase or decrease in bullying behavior, and to achieve the research objectives, the bullying behavior scale was used by Dr. The fourth year, Department of Sociology, Faculty of Arts, University of Damascus, and the sample size was (90) individuals. The results of the study showed, according to the variables presented by the research, that there is a statistically significant relationship between the gender variable and the rates of electronic bullying, and there is no statistically significant relationship between the time an individual spends on social media and the rate of increase of bullying at the significance level (0.05) The statistical study was done according to the test (Student)